2023
DOI: 10.3390/nano13142051
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption Mechanism of Hydrogen on FeO Crystal Surfaces: A Density Functional Theory Study

Abstract: The hydrogen-based direct reduction of iron ores is a disruptive routine used to mitigate the large amount of CO2 emissions produced by the steel industry. The reduction of iron oxides by H2 involves a variety of physicochemical phenomena from macroscopic to atomistic scales. Particularly at the atomistic scale, the underlying mechanisms of the interaction of hydrogen and iron oxides is not yet fully understood. In this study, density functional theory (DFT) was employed to investigate the adsorption behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…They found that H 2 molecules tend to physically adsorb at the top positions of Fe atoms, while Fe atoms on the FeO surface act as active sites catalyzing the dissociation of H 2 . The dissociated H atoms are more inclined to form chemical bonds with surface O atoms [33]. Dadfarnia et al proposed a modified hydrogen transport model and concluded that dislocations contribute to increasing the local hydrogen concentration before crack initiation [34].…”
Section: Introductionmentioning
confidence: 99%
“…They found that H 2 molecules tend to physically adsorb at the top positions of Fe atoms, while Fe atoms on the FeO surface act as active sites catalyzing the dissociation of H 2 . The dissociated H atoms are more inclined to form chemical bonds with surface O atoms [33]. Dadfarnia et al proposed a modified hydrogen transport model and concluded that dislocations contribute to increasing the local hydrogen concentration before crack initiation [34].…”
Section: Introductionmentioning
confidence: 99%